Out-of-hospital rescue medication in dogs with emergency seizure disorders: an owner perspective - Kähn, Charlotte; Bhatti, Sofie F. M.; Meller, Sebastian; Meyerhoff, Nina; Volk, Holger A.; Charalambous, Marios (Frontiers in Veterinary Science, 2023)
Background: Emergency seizure disorders such as status epilepticus and cluster seizures are unlikely to cease spontaneously while prolonged seizure activity become progressively more resistant to treatment. Early administration of rescue medication in canine epileptic patients, in particular benzodiazepines, at seizure onset by the owners can be life-saving and brain protecting. Clinical studies in dogs evaluating the use of rescue medication in hospital environment exist, however, the owner perspective has not been assessed to date. Hypothesis/objectives: To evaluate the use of rescue medication in dogs with seizure emergencies by the owner at home. Method: Observational study based on online surveys of owners of dogs with emergency seizure disorders. Results: The questionnaire was answered by 1563 dog owners, of which 761 provided complete and accurate answers suitable for analysis. Of these, 71% administered diazepam, 19% midazolam, 6% levetiracetam, 3% lorazepam, and 4% more than one rescue or other medication. Overall, the success rates based on owners' perspective for intranasal midazolam and rectal diazepam were 97% and 63%, respectively. Owners reported a compliance level of 95% and 66% for intranasal midazolam and rectal diazepam administration, respectively. Conclusions and clinical importance: Even though rectal diazepam was the most used rescue medication in this survey population, intranasal midazolam was perceived by the owners as a better option regarding effectiveness, time to seizure cessation and owner compliance.